Happiness, growth, and the life Cycle - Easterlin, Richard A.; Edited by Hinte, Holger and Zimmermann, Klaus F. (New York Oxford University Press, 2016)
The second in a series of books published with the IZA and honoring the work of its annual prize winners in labour economics. It presents Richard Easterlin's outstanding research on the analysis of subjective well-being, and on the relationship between demographic developments and economic outcomes.
Include Index and References
Keywords: Economic development--Psychological aspects -- Happiness--Economic aspects